secx cscx = 1/ cosx 1/sinx = (sinx cosx) / sinx*cosx= 1/ sinx*cosx

secx cscx = 1/ cosx 1/sinx = (sinx cosx) / sinx*cosx= 1/ sinx*cosx

(5) RHS = (cosx sinx)^-2

tanx = sinx / cosx

cotx = cosx / sinx

n2

( tanx cotx ) = ( sinx/cosx cosx/sinx) = [ (sinx cosx) / sinx*cosx ] =1/ sinx*cosx

couse sinx cosx=1

(3) RHS = sec^2x csc^2x = (1/cos^2 1/sin^2)^2

(3) RHS = sec^2x csc^2x = (1/cos^2 1/sin^2)^2

(5) RHS = (cosx sinx)^-2

(6) LHS = RHS

(5) RHS = (cosx sinx)^-2

secx = 1/ cosx

cscx = 1/ sinx

(3) RHS = sec^2x csc^2x = (1/cos^2 1/sin^2)^2

J = (tan x cot x)

(tanx cotx)^2 =

tan^2x 2tanxcotx cot^2x =

tan^2x 2(sinx/cosx)(cosx/sinx) cot^2x =

tan^2x 2 cot^2x =

tan^2x 1 1 cot^2x =

sec^2x csc^2x qed

tanx = sinx / cosx

cotx = cosx / sinx

n2

( tanx cotx ) = ( sinx/cosx cosx/sinx) = [ (sinx cosx) / sinx*cosx ] =1/ sinx*cosx

couse sinx cosx=1

secx = 1/ cosx

cscx = 1/ sinx

(6) LHS = RHS

This post is last updated on hrtanswers.com at Date : 1st of September – 2022